Indikátory sociálního pilíře udržitelného rozvoje na lokální úrovni - Kučerová, Zita (Vysoké učení technické v Brně. Fakulta architektury)
Cílem práce bylo najít odpověď na otázky, zda lze monitorovat sociální soudržnost (kohezi) obce a čím tuto kohezi, která je jedním ze základních pilířů udržitelného rozvoje, měřit. Byl proveden rozbor přístupů a měření udržitelného rozvoje sociálního pilíře v mezinárodním i českém prostředí. Sociální pilíř byl identifikován a popsán i pro lokální úroveň. V rámci sociálního pilíře udržitelného rozvoje na úrovni obce jsou navrženy tři hlavní tématické bloky: • Kvalita sociálního prostředí obce • Sociodemografická struktura obyvatel obce • Spokojenost a participace na věcech veřejných. Tato témata by měla být monitorována indikátorovou sadou, navrženou v této práci. Jejím cílem bylo pokrýt všechny dimenze sociální koheze, které jsou opodstatněné a významné ve vazbě na procesy územního plánování. Tyto indikátory lze sledovat v přímě vazbě na populační velikost a regionální význam sledované územní jednotky na lokální úrovni a nejsou vytrženy z konceptu sledování indikátorů udržitelného rozvoje na dalších územně vyšších úrovních. Výsledky, analýza a interpretace dosažených hodnot by se mohly stát jedním z podkladů pro „rozbor udržitelného rozvoje území“ (součást nástrojů územního plánování dle současné právní úpravy), reprezentující sociální pilíř. Všechny jevy a procesy musí být zároveň hodnoceny v kontextu dalších pilířů udržitelného rozvoje a poté by se měly stát též vhodným nástrojem k měření naplňování cílů územního plánování.

The aim of the thesis is to find the answer, whether it is plausible to monitor social cohesion of the municipality and how to measure this cohesion, which is one of the essential pillars of sustainable development. In order to find out, analysis of approaches and measurements of the sustainable development social pillar in international and Czech environment was carried out. Social pillar was identified and described also at the local level. Within the framework of the sustainable development social pillar at the municipal level three main thematic blocks are proposed: • Social environment quality of the municipality • Social-demographic population structure of the municipality • Contentment and participation in the public affairs These themes should be monitored by the set of indicators proposed in this thesis. It aimed to cover all dimensions of social cohesion which are significant and well-founded in the context of the territorial planning process. These indicators can be followed in the direct relationship with the population size and regional importance of the observed territorial unit at the local level and they are not separated from the concept of indicators monitoring at other – territorially higher – levels. Outcomes, analysis and interpretation of attained values could become the basis for the “territorial sustainable development analysis” (part of territorial planning instruments according to contemporary legal regulations), representing social pillar. All phenomenon and processes must be evaluated in the context with other sustainable development pillars and afterwards they should become another suitable instrument for measurement of the fulfilling the territorial planning aims.
Indicatours of sustainable development social pillar at the local level
Keywords: Indikátory udržitelného rozvoje; kvalita sociálního prostředí; udržitelný rozvoj; sociální pilíř; sociální soudržnost; spokojenost; struktura obyvatel; územní plánování; Sustainable development indicators; quality of social environment; sustainable development; social pillar; social cohesion; contentment; population structure; territorial planning